A computational approach to analyze the missense mutations in human angiogenin variants leading to amyotrophic lateral sclerosis - K. Sreevishnupriya; Ramalingar Rajasekaran (Bangladesh Pharmacological Society, 2013)
The most detrimental missense mutations of angiogenin causing Amyotrophic lateral sclerosis were identified computationally and the substrate binding efficiencies of these mutations were also analyzed. Out of 12 variants, I-Mutant 2.0, SIFT and PolyPhen programs identified 3 variants that were less stable, deleterious and damaging respectively. Modeling of these 3 variants was performed to understand the change in their conformations with respect to the native angiogenin by computing their RMSD and Total energy. The native and the 3 mutants were docked with ribonuclease inhibitor to explain the binding efficiencies of those detrimental missense mutations. The loss of binding affinity with their interacting protein namely ribonuclease inhibitor was investigated by computing the flexibility of binding amino acids of angiogenin and computing the binding free energy (ΔG) between native and mutant complexes.